TANGGUNG JAWAB DOKTER DALAM MELAKUKAN ABORSI TANPA SEIJIN IBU YANG MENGANDUNG ATAU KELUARGA DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA - Tanti Kirana Utami; Aji Mulyana (Universitas Suryakancana, 2015)
A doctors liable criminally to do an abortion without any permission orexplanation before an abortion to the pregnant or the family. A doctor’s Criminalliability that does an abortion as a medical indication without any permissionfrom the pregnant mother or the family is considered as a subjection to criminalpenalties if the abortion is not done under emergency situation. Otherwise, doctoris not liable to the law. The writing uses juridical normative approach andobserved using primary, secondary and tertiary literature. The technique ofcollecting data is obtained by researching the literature. After observing, theliterature is analyzed by qualitative method. The result of this research is that anabortion case as a medical indication without any permission from the pregnantmother or the family is subject to criminal penalties, civil liability andadministrative sanctions. It is stipulated in criminal code and civil code, so thatabortion is absolutely prohibited.Keywords: Abortions, Responsibility Doctors, Without Permission Mother orFamily.